Multifunctional self-repairing well cementation cement slurry system as well as preparation method and application thereof
The multifunctional self-healing cement slurry system solves the problems of self-healing, corrosion prevention, and elasticity of cement sheaths in high-concentration supercritical carbon dioxide environments, achieving efficient self-healing and long-term integrity of the cement sheath.
Patent Information
- Application Number
- CN202511162207.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-28
AI Technical Summary
Existing technologies are insufficient to meet the integrity requirements of cement sheaths in high-concentration supercritical carbon dioxide environments, and cannot simultaneously achieve rapid self-repair, corrosion resistance, and elasticity, leading to wellbore seal failure.
A multifunctional self-healing cement slurry system is adopted, which includes cement, carbon dioxide self-healing agent, solid toughening corrosion inhibitor, liquid elastic anti-channeling agent and other components. Through synergistic effect, it improves corrosion resistance and elastic toughness, and achieves rapid self-healing.
Under high-concentration supercritical carbon dioxide conditions, the self-repair rate of cement sheath cracks exceeds 90%, and it has strong corrosion resistance and good elasticity and toughness, ensuring the long-term integrity of cement sheath.
Smart Images

Figure BDA0005555575570000121
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cementing slurry technology, and relates to a multifunctional self-healing cementing slurry system, its preparation method and application, especially a multifunctional self-healing cementing slurry system and its preparation method for high acid scenarios such as CCUS / CCS, gas storage facilities, carbon dioxide flooding for enhanced oil recovery, development and disposal of high acid oil and gas fields. Background Technology
[0002] In high-acid scenarios such as CCUS (Carbon Capture, Utilization, and Sequestration) / CCS (Carbon Capture and Sequestration), gas storage facilities, CO2 flooding for enhanced oil recovery, development of acidic oil and gas fields, and abandoned wells, the CO2 content often exceeds 90% and is in a supercritical state. Currently, cementing operations in such high-acid wells mainly use silicate oil well cement, which becomes alkaline after hydration, while the high concentration of supercritical CO2 injected underground is acidic, causing severe corrosion of the cement sheath, leading to increased porosity and decreased mechanical properties. Furthermore, the CO2 injection process is accompanied by changes in wellbore temperature and pressure, making the cement sheath more susceptible to stress-induced wellbore seal integrity failure. To overcome the technical challenge of cement sheath integrity failure in high-concentration supercritical CO2 environments and prevent CO2 from escaping back into the atmosphere after underground storage, cementing slurry systems for high-acid scenarios must possess multiple characteristics, including rapid response to CO2 to repair cracks, resistance to high-concentration supercritical CO2 corrosion, and good elasticity and toughness, thereby ensuring the lifecycle integrity of cement sheaths in high-acid scenarios.
[0003] Existing technologies enhance the corrosion resistance of cement stone through nano-silica, latex, epoxy resin, and their composite materials. Modified adhesive powder, fibers, and epoxy resin improve the elasticity and toughness of cement stone, while calcium carbonate whiskers and graphene oxide achieve self-healing effects on cement stone cracks in CCUS wells. The anti-corrosion materials described in published patents mainly consist of auxiliary cementing materials (such as slag, microsilica, fly ash, etc.), organic anti-corrosion materials (such as modified latex powder, modified resin), and inorganic anti-corrosion materials (such as fibers). The elasticity and toughness materials in the aforementioned published patents mainly consist of inorganic toughening materials (such as sodium sulfate, potassium titanate whiskers, carbon fiber, etc.) and organic toughening materials (such as soluble fibers, granules, resin powder, etc.). The self-healing materials in the aforementioned published patents that react with carbon dioxide—calcium carbonate whiskers, water-soluble linear diamine, and epoxide—react with carbon dioxide to form reaction products that fill cracks and achieve self-healing; coal, petroleum coke, and rubber expand and self-heal upon exposure to carbon dioxide.
[0004] Existing technologies mainly focus on elastic-toughness cement grout, corrosion-resistant cement grout, and self-healing cement grout, respectively. Their applicability is limited to low carbon dioxide concentrations (<10%), low temperatures (50–90℃), and a relatively narrow density range (1.8–1.9 g / cm³). 3It is difficult to combine adaptability to high-concentration (>90%) supercritical carbon dioxide environment, rapid self-repair capability in the presence of carbon dioxide, strong corrosion resistance and excellent elasticity and toughness, and therefore cannot meet the requirements for long-term integrity of cement sheath in high acid environment. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a multifunctional self-healing cement slurry system, its preparation method, and its application.
[0006] Specifically, the multifunctional self-healing cement slurry system provided by this invention includes: cement, carbon dioxide self-healing agent, solid toughening corrosion inhibitor, liquid elastic anti-channeling agent, fluid loss reducing agent, defoamer, dispersant, retarder, and water.
[0007] The aforementioned multifunctional self-healing cement slurry system, by weight, comprises: 100 parts cement, 2-18 parts carbon dioxide self-healing agent, 5-30 parts solid toughening corrosion inhibitor, 3-15 parts liquid elastic anti-channeling agent, 3-9 parts fluid loss reducing agent, 0.25-2 parts defoamer, 0.1-2.5 parts dispersant, 0.5-4.0 parts retarder, and 42-45 parts fresh water.
[0008] The aforementioned multifunctional self-healing cement slurry system uses G / H grade high sulfur-resistant silicate cement that meets API standards.
[0009] In the aforementioned multifunctional self-healing cement slurry system, the self-healing agent in the presence of carbon dioxide is a mixture of rubber particles and gypsum, or a mixture of rubber particles and metal oxides, or a mixture of rubber particles, gypsum, and metal oxides.
[0010] In the aforementioned multifunctional self-healing cement slurry system, the mass ratio of the coated rubber particles, the gypsum, and the metal oxide is 3-15:2-10:1-5.
[0011] The aforementioned multifunctional self-healing cement slurry system includes a liquid elastic anti-channeling agent comprising at least one of latex and resin.
[0012] In the aforementioned multifunctional self-healing cement slurry system, the fluid loss reducing agent is AMPS polymer.
[0013] In the aforementioned multifunctional self-healing cement slurry system, the dispersant is selected from one or two of sulfonated aldehyde-ketone condensate dispersants and polycarboxylic acid dispersants.
[0014] The aforementioned multifunctional self-healing cement slurry system includes at least one type of retarder: organophosphate retarder and polymer retarder.
[0015] In the aforementioned multifunctional self-healing cement slurry system, the defoamer includes any one or more of phosphate ester defoamers, polyether defoamers, and organosilicon defoamers.
[0016] The present invention provides a method for preparing a multifunctional self-healing cement slurry system, comprising:
[0017] (1) Mix cement, carbon dioxide self-healing agent and solid toughness corrosion inhibitor into a mixed ash according to the proportion;
[0018] (2) Dissolve the liquid elastic anti-channeling agent, water loss reducing agent, dispersant, retarder, and defoamer in water according to the proportion to obtain mixed water;
[0019] (3) Under the first speed stirring, the mixed ash is added to the mixed water, and then stirred at the second speed to obtain a multifunctional self-healing cement slurry system.
[0020] This invention also provides the application of the above-mentioned multifunctional self-healing cement slurry system in CCUS, CCS, gas storage facilities, carbon dioxide flooding for enhanced oil recovery, development of acidic oil and gas fields, and high acidity scenarios of abandoned wells.
[0021] The technical solution of the present invention has the following beneficial effects:
[0022] (1) The multifunctional self-healing cement slurry system provided by the present invention effectively improves the corrosion resistance, elasticity and toughness and gas channeling prevention of cement stone by giving full play to the synergistic effect of solid toughness anti-corrosion materials and liquid elastic anti-channeling materials. Thus, the cement sheath has multiple characteristics such as being applicable to >90% high concentration supercritical carbon dioxide, rapid response to carbon dioxide self-healing, strong corrosion resistance and good elasticity and toughness, high temperature and high pressure resistance and wide applicability, providing strong protection for the integrity of the cement sheath throughout its entire life cycle.
[0023] (2) The multifunctional self-healing cement slurry system provided by the present invention gives the cement sheath the characteristic of rapid response to carbon dioxide. Under the conditions of temperature of 180℃, pressure of 40Mpa and concentration of 100% carbon dioxide, the self-healing rate of cement sheath cracks exceeds 90% in 12 hours, realizing the self-healing of cement stone cracks.
[0024] (3) The multifunctional self-healing cement slurry system provided by this invention is suitable for cement slurry densities ranging from 1.50 to 2.0 g / cm³. 3 Conditions requiring a temperature range of 30–180℃ and a carbon dioxide content exceeding 90%.
[0025] (4) The multifunctional self-healing cement slurry system provided by the present invention is simple to prepare and easy to operate. It can be mixed at room temperature and is suitable for industrial production and field application. Detailed Implementation
[0026] To fully understand the purpose, features, and effects of this invention, the following detailed embodiments are provided. Except as described below, the process methods of this invention employ conventional methods or apparatus in the art. Unless otherwise specified, the terms and expressions used below have the meanings commonly understood by those skilled in the art.
[0027] When a range of values is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0028] Specifically, the multifunctional self-healing cement slurry system provided by this invention includes: oil well cement, carbon dioxide self-healing agent, solid toughening corrosion inhibitor, liquid elastic anti-channeling agent, fluid loss reducing agent, dispersant, retarder, defoamer, and water.
[0029] In the multifunctional self-healing cement slurry system provided by this invention, the carbon dioxide self-healing agent can reduce the elastic modulus of the cement stone, significantly improve its elasticity and toughness, and reduce the occurrence of cement stone damage. Furthermore, when microcracks or micro-annular gaps occur in the cement stone, the agent rapidly expands upon contact with carbon dioxide, achieving self-repair of these microcracks or micro-annular gaps. This helps improve the corrosion resistance and gas channeling prevention capabilities of the cement stone. The solid toughening corrosion inhibitor can replace part of the silicate oil well cement dosage, reducing the alkalinity of the cement stone. Through particle size distribution technology, it increases the solid volume fraction of the cement slurry and the density of the cement stone, thereby reducing the corrosion rate and gas channeling risk. Combined with a liquid elastic anti-channeling agent, it can cover the surface of cement hydration product particles, forming a protective film that improves the density and bonding strength of the cement stone, effectively reducing its porosity and permeability, increasing the resistance to formation fluid gas intrusion, and further improving the corrosion resistance and gas channeling prevention capabilities of the cement stone, thus ensuring the long-term integrity of the cement sheath in CCS / CCUS wells.
[0030] The components of the multifunctional self-healing cement slurry system of the present invention will be described in detail below.
[0031] Oil well cement
[0032] Oil well cement is the fundamental cementing material and core component for performance control in cementing slurries, enabling them to perform their engineering functions. In cementing slurry systems, oil well cement is the main solid component, while other components are admixtures or additives used to regulate its properties, ultimately achieving the functions of sealing the formation, supporting the casing, and maintaining the long-term integrity of the wellbore.
[0033] In some preferred embodiments, the cement used in this invention is API grade G / H high sulfur-resistant silicate cement.
[0034] Self-healing agent in contact with carbon dioxide
[0035] Carbon dioxide self-healing agents can reduce the elastic modulus of cement stone, significantly improve its elasticity and toughness, and reduce the occurrence of cement stone damage. They can also rapidly expand upon contact with carbon dioxide when microcracks or micro-annular gaps occur in the cement stone, thus enabling the self-repair of these microcracks or micro-annular gaps. This helps to improve the corrosion resistance and gas channeling prevention capabilities of the cement stone.
[0036] In some preferred embodiments, the carbon dioxide self-healing agent is composed of rubber particles, gypsum, and metal oxides.
[0037] The rubber particles are nitrile rubber particles with a particle size of 100-300μm.
[0038] The metal oxide is, for example, passivated magnesium oxide; the passivation process can be carried out according to existing technology, and the present invention does not specifically limit it.
[0039] More preferably, the self-healing agent in the presence of carbon dioxide is any one of 1)-3) below, and is stirred and mixed evenly at room temperature. The mass ratio of the rubber particles, the gypsum, and the metal oxide is 3-15:2-10:1-5.
[0040] 1) A mixture of rubber granules and gypsum;
[0041] 2) A mixture of rubber granules and metal oxides;
[0042] 3) A mixture of rubber granules, gypsum and metal oxides.
[0043] In some preferred embodiments, based on 100 parts by weight of cement, the proportion of carbon dioxide self-healing agent in the multifunctional self-healing cement slurry system of the present invention is 2 to 18 parts.
[0044] Optionally, the self-healing agent in the presence of carbon dioxide is prepared in the following proportions: 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, or 18 parts.
[0045] In practice, when the proportion of carbon dioxide self-healing agent is less than 2 parts, the self-healing rate of cement stone cracks is slow; when the proportion of carbon dioxide self-healing agent is greater than 18 parts, the cement slurry mixing ability is poor, the cementing time is long, and it does not meet the requirements of on-site operation.
[0046] More preferably, based on 100 parts by weight of cement, the proportion of carbon dioxide self-healing agent in the multifunctional self-healing cement slurry system of the present invention is 6 to 14 parts.
[0047] Solid toughness corrosion inhibitor
[0048] Solid toughening corrosion inhibitors can replace part of the amount of silicate oil well cement, thereby reducing the alkalinity of cement stone. Through particle size distribution technology, they can increase the solid volume fraction of cement slurry and the compactness of cement stone, thereby reducing the corrosion rate of cement stone and the risk of gas channeling.
[0049] As an example, the solid toughening corrosion inhibitor was purchased from Blue Ocean Boda Technology Co., Ltd., and its brand name is C-AC10S.
[0050] In some preferred embodiments, the proportion of solid toughening corrosion inhibitor in the multifunctional self-healing cement slurry system of the present invention is 5 to 30 parts per 100 parts by weight of cement.
[0051] Optionally, the solid toughening preservative is prepared in proportions of 5, 7, 9, 11, 13, 15, 17, 19, 20, 22, 24, 26, 28 or 30 parts.
[0052] In practice, when the proportion of solid toughening corrosion inhibitor is less than 5 parts, the anti-corrosion effect is poor; when the proportion of solid toughening corrosion inhibitor is greater than 30 parts, the toughness of cement stone decreases significantly.
[0053] More preferably, in the multifunctional self-healing cement slurry system of the present invention, the proportion of solid toughening corrosion inhibitor is 10 to 25 parts per 100 parts by weight of cement.
[0054] Water loss reducer
[0055] Fluid loss reducers can reduce the amount of cement slurry lost during the pumping process to the formation-casing annulus, thus preventing excessive slurry loss, premature setting, and formation contamination by the filtrate.
[0056] In some preferred embodiments, the water loss reducing agent is an AMPS polymer-based water loss reducing agent, for example, which can be purchased from Blue Ocean Boda Technology Co., Ltd., with brand names C-FL80L and C-FL86L, or both.
[0057] In some preferred embodiments, based on 100 parts by weight of cement, the multifunctional self-healing cement slurry system of the present invention contains 3 to 9 parts by weight of the fluid loss reducing agent.
[0058] Optionally, the water loss reducing agent is expressed in parts by weight of 3, 4, 5, 6, 7, 8, or 9.
[0059] In practice, when the proportion of the water loss reducing agent is less than 3 parts, the water loss reduction effect is limited and the water loss of the cement slurry is high; when the proportion of the water loss reducing agent is greater than 9 parts, the cement slurry is difficult to mix and has poor rheological properties.
[0060] More preferably, based on 100 parts by weight of cement, the multifunctional self-healing cement slurry system of the present invention contains 4 to 7 parts by weight of the fluid loss reducing agent.
[0061] Defoamer
[0062] During the cement mixing process, on the one hand, the generation of air bubbles in the cement slurry is suppressed; on the other hand, a small number of air bubbles are quickly eliminated after they are generated, so as to avoid the cement slurry containing a large number of air bubbles, thereby improving the cement mixing capacity of the cement slurry and ensuring that cement slurry with the designed density can be obtained.
[0063] In some preferred embodiments, the defoamer is selected from any one or more of phosphate ester defoamers, polyether defoamers, and silicone defoamers.
[0064] For example, phosphate ester defoamers can be purchased from Blue Ocean Boda Technology Co., Ltd., under the brand name C-DF60L.
[0065] For example, polyether defoamers can be purchased from Blue Ocean Boda Technology Co., Ltd., under the brand name C-DF63L.
[0066] For example, silicone defoamers can be purchased from Blue Ocean Boda Technology Co., Ltd., brand name C-DF62L.
[0067] In some preferred embodiments, the defoamer in the multifunctional self-healing cement slurry system of the present invention is 0.25 to 2 parts by weight, based on 100 parts by weight of cement.
[0068] Optionally, the defoamer is present in parts by weight of 0.25 parts, 0.5 parts, 1 part, 1.5 parts or 2 parts.
[0069] In practice, when the proportion of defoamer is less than 0.25 parts, the defoaming effect is poor; when the proportion of defoamer is greater than 2 parts, the defoaming effect does not change much, but the amount used is larger, and the economy is greatly reduced.
[0070] More preferably, in the multifunctional self-healing cement slurry system of the present invention, the defoamer is 0.5 to 1 part by weight, based on 100 parts by weight of cement.
[0071] dispersant
[0072] Dispersants, also known as drag reducers, can disperse cement slurry, reduce its consistency, and improve its pumpability.
[0073] In some preferred embodiments, the dispersant is selected from one or both of sulfonated aldehyde-ketone condensate dispersants and polycarboxylic acid dispersants.
[0074] For example, sulfonated aldehyde-ketone condensate dispersants are available from Blue Ocean Boda Technology Co., Ltd., under the brand name C-F41L.
[0075] For example, polycarboxylate dispersants can be purchased from Blue Ocean Boda Technology Co., Ltd., under the brand names C-F45L and C-F46L, or both.
[0076] In some preferred embodiments, the dispersant in the multifunctional self-healing cement slurry system of the present invention is 0.1 to 2.5 parts by weight, based on 100 parts by weight of cement.
[0077] Optionally, the dispersant is present in parts by weight of 0.1, 0.5, 1.0, 1.5, 2.0, or 2.5.
[0078] In practice, when the proportion of dispersant is less than 0.1 parts, the drag reduction effect is not good; when the proportion of dispersant is greater than 2.5 parts, the cement paste is unstable or the retarding effect is serious.
[0079] More preferably, in the multifunctional self-healing cement slurry system of the present invention, the dispersant is 0.5 to 1.5 parts by weight, based on 100 parts by weight of cement.
[0080] Liquid elastic anti-channeling agent
[0081] Liquid elastic anti-channeling agent can cover the surface of cement hydration product particles to form a protective film, improve the density and bonding strength of cement stone, effectively reduce the porosity and permeability of cement stone, increase the resistance to formation fluid gas intrusion, and improve the corrosion resistance and gas channeling prevention of cement stone.
[0082] In some preferred embodiments, the liquid elastic anti-channeling agent includes at least one of latex and resin liquid.
[0083] For example, the latex can be purchased from Blue Ocean Boda Technology Co., Ltd., under the brand name C-GS21L.
[0084] For example, the resin liquid can be purchased from Blue Ocean Boda Technology Co., Ltd., with the brand name C-RS10L.
[0085] In some preferred embodiments, the liquid elastic anti-channeling agent in the multifunctional self-healing cement slurry system of the present invention is 3 to 15 parts by weight, based on 100 parts by weight of cement.
[0086] Optionally, the liquid elastic anti-channeling agent is present in parts by weight of 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15.
[0087] In practice, when the proportion of liquid elastic anti-channeling agent is less than 3 parts, the anti-channeling effect is not good; when the proportion of liquid elastic anti-channeling agent is greater than 15 parts, demulsification is likely to occur, leading to instability of cement paste.
[0088] More preferably, in the multifunctional self-healing cement slurry system of the present invention, the dispersant is 5 to 10 parts by weight, based on 100 parts by weight of cement.
[0089] Retarder
[0090] Retarders can effectively prolong or maintain the time that cement slurry remains in a liquid state and is pumpable.
[0091] In some preferred embodiments, the retarder includes at least one of organophosphate retarder and polymer retarder.
[0092] For example, organophosphate retarder can be purchased from Blue Ocean Boda Technology Co., Ltd., brand name C-R21L.
[0093] For example, polymeric retarder can be purchased from Blue Ocean Boda Technology Co., Ltd., under the brand name C-R40L.
[0094] In some preferred embodiments, the retarder in the multifunctional self-healing cement slurry system of the present invention is 0.5 to 4.0 parts by weight, based on 100 parts by weight of cement.
[0095] Optionally, the retarder is present in parts by weight of 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, or 4.0.
[0096] In practice, when the proportion of retarder is less than 0.5 parts, the retarding effect is limited and insufficient to extend the thickening time of cement paste; when the proportion of retarder is greater than 4.0 parts, it is difficult to regulate the development of compressive strength of cement paste.
[0097] More preferably, in the multifunctional self-healing cement slurry system of the present invention, the retarder has a weight of 0.5 to 2.0 parts per 100 parts by weight of cement.
[0098] On the other hand, the present invention also provides a method for preparing a multifunctional self-healing cement slurry system, comprising:
[0099] (1) Mix cement, carbon dioxide self-healing agent and solid toughness corrosion inhibitor into a mixed ash according to the proportion;
[0100] (2) Dissolve the liquid elastic anti-channeling agent, water loss reducing agent, dispersant, retarder, and defoamer in water according to the proportion to obtain mixed water;
[0101] (3) Under the first speed stirring, the mixed ash is added to the mixed water, and then stirred at the second speed to obtain a multifunctional self-healing cement slurry system.
[0102] The proportions and types of cement, carbon dioxide self-healing agent, solid toughening corrosion inhibitor, liquid elastic anti-channeling agent, fluid loss reducing agent, dispersant, retarder, defoamer, and water are consistent with those described in the multifunctional self-healing cement slurry system provided in the first aspect of this invention, and will not be repeated here.
[0103] In some preferred embodiments, according to the cementing test standard GB / T 19139-2012, the first rotation speed is 4000±200 r / min, and the stirring time is 15-40 seconds; the second rotation speed is 12000±500 r / min, and the stirring time is 10-15 seconds.
[0104] The multifunctional self-healing cement slurry system provided by this invention has a simple and easy preparation method, which can be achieved by stirring and mixing at room temperature. It is suitable for industrial production and field application.
[0105] The multifunctional self-healing cement slurry system prepared according to the method of the present invention endows the cement sheath with the characteristic of rapid response to carbon dioxide. Under the conditions of temperature of 180°C, pressure of 40 MPa, and concentration of 100% carbon dioxide, the self-healing rate of cement sheath cracks exceeds 90% after 12 hours, realizing the self-repair of cement stone cracks. This meets the application requirements of cement sheaths in high acidic scenarios such as CCUS, CCS, gas storage, carbon dioxide flooding for enhanced oil recovery, development of acidic oil and gas fields, and abandoned wells.
[0106] Example
[0107] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments, unless otherwise specified, are performed according to conventional methods and conditions.
[0108] The raw materials used in the following examples are from the following sources:
[0109] Oil well cement was purchased from Zibo Zhongchang Special Cement Co., Ltd.; solid toughening corrosion inhibitor was purchased from LanHai Boda Technology Co., Ltd., brand name C-AC10S; defoamer (organosilicon type) was purchased from LanHai Boda Technology Co., Ltd., brand name C-DF62L; dispersant (polycarboxylic acid type) was purchased from LanHai Boda Technology Co., Ltd., brand name C-F46L; fluid loss reducing agent (AMPS polymer type) was purchased from LanHai Boda Technology Co., Ltd., brand name C-FL80L; retarder (polymer type) was purchased from LanHai Boda Technology Co., Ltd., brand name C-R40L. Latex was purchased from LanHai Boda Technology Co., Ltd., brand name C-GS21L; resin solution was purchased from LanHai Boda Technology Co., Ltd., brand name C-RS10L.
[0110] The preparation method of the carbon dioxide self-healing agent used in the example is as follows:
[0111] (1) Weigh 50g of rubber granules, 35g of gypsum and 15g of passivated magnesium oxide, and screen out any foreign matter that may enter. The screen mesh size is ≥40 mesh.
[0112] (2) The components, including the rubber particles, gypsum, and metal oxides, are poured into a mixing machine and thoroughly mixed physically in the mixing machine to ensure uniformity, thereby obtaining the self-healing agent for cementing slurry in the presence of carbon dioxide.
[0113] Example 1:
[0114] Weigh 100 parts by weight of cement, 2 parts by weight of carbon dioxide self-healing agent, and 10 parts by weight of solid toughening corrosion inhibitor and dry mix them to form a mixed ash. Measure 45 parts by weight of fresh water, 0.5 parts by weight of defoamer, 0.5 parts by weight of dispersant, 5 parts by weight of water loss reducer, 4 parts by weight of latex, and 0.1 parts by weight of retarder and dissolve them in water. Then, put the mixed water into a mixing cup and use a corrugated mixer to rotate at low speed (4000±200 r / min). Add the weighed mixed ash evenly within 15 seconds. After all the mixed ash is poured into the mixed water, cover the mixing cup and stir at high speed (12000±500 r / min) for 35 seconds to obtain the final product.
[0115] Example 2:
[0116] Weigh 100 parts by weight of cement, 3 parts by weight of carbon dioxide self-healing agent, and 12 parts by weight of solid toughening corrosion inhibitor and dry mix them to form a mixed ash. Measure 44 parts by weight of fresh water, 0.5 parts by weight of defoamer, 1 part by weight of dispersant, 4 parts by weight of water loss reducer, 4 parts by weight of resin liquid, and 0.3 parts by weight of retarder and dissolve them in water. Then, put the mixed water into a mixing cup and use a corrugated mixer to rotate at low speed (4000±200r / min). Add the weighed mixed ash evenly within 15 seconds. After all the mixed ash is poured into the mixed water, cover the mixing cup and stir at high speed (12000±500r / min) for 35 seconds to obtain the final product.
[0117] Example 3:
[0118] Weigh 100 parts by weight of cement, 4 parts by weight of carbon dioxide self-healing agent, and 15 parts by weight of solid toughening corrosion inhibitor and dry mix them to form a mixed ash. Measure 43 parts by weight of fresh water, 0.8 parts by weight of defoamer, 1.5 parts by weight of dispersant, 5 parts by weight of water loss reducer, 5 parts by weight of resin liquid, and 0.4 parts by weight of retarder and dissolve them in water. Then, put the mixed water into a mixing cup and use a corrugated mixer to rotate at low speed (4000±200r / min). Add the weighed mixed ash evenly within 15 seconds. After all the mixed ash is poured into the mixed water, cover the mixing cup and stir at high speed (12000±500r / min) for 35 seconds to obtain the final product.
[0119] Example 4:
[0120] Weigh 100 parts by weight of cement, 5 parts by weight of carbon dioxide self-healing agent, and 18 parts by weight of solid toughening corrosion inhibitor and dry mix them to form a mixed ash. Measure 42 parts by weight of fresh water, 1 part by weight of defoamer, 1.5 parts by weight of dispersant, 6 parts by weight of water loss reducer, 5 parts by weight of resin liquid, and 0.6 parts by weight of retarder and dissolve them in water. Then, put the mixed water into a mixing cup and use a corrugated mixer to rotate at low speed (4000±200 r / min). Add the weighed mixed ash evenly within 15 seconds. After all the mixed ash is poured into the mixed water, cover the mixing cup and stir at high speed (12000±500 r / min) for 35 seconds to obtain the final product.
[0121] Performance testing
[0122] The performance of the multifunctional self-healing cement slurry systems prepared in Examples 1-4 was tested according to the cementing test standard GB / T 19139-2012. The test results are shown in Table 1.
[0123] Table 1 Performance test results of the multifunctional self-healing cementing slurry system of the present invention
[0124]
[0125] It can be seen that the multifunctional self-healing cement slurry of this invention has low water loss, adjustable thickening time, and compressive strength that meets the requirements of cementing construction. The self-healing rate of the cement stone exceeds 91% after 12 hours under 100% carbon dioxide conditions, the corrosion depth after 14 days is less than 1.3 mm, and the elastic modulus is less than 6.0 GPa, indicating that the multifunctional self-healing cement slurry not only has good self-healing ability in the presence of carbon dioxide but also possesses good corrosion resistance and elasticity. Furthermore, all the properties of conventional cement slurries meet the requirements of on-site cementing operations.
[0126] In summary, the multifunctional self-healing cement slurry of the present invention not only has excellent construction performance, but also the cement stone formed after solidification possesses multiple characteristics such as applicability to high concentrations (>90%) of supercritical carbon dioxide, rapid self-healing response to carbon dioxide, strong corrosion resistance, good elasticity and toughness, and wide applicability. It can effectively solve the technical problems of cement sheath corrosion and sealing integrity failure in high acidic scenarios such as CCUS / CCS, gas storage facilities, carbon dioxide flooding for enhanced oil recovery, development and disposal of acidic oil and gas fields, and ensure the integrity of cement sheath throughout its entire life cycle.
[0127] The present invention has been disclosed above with reference to preferred embodiments. However, those skilled in the art should understand that these embodiments are merely illustrative of the invention and should not be construed as limiting its scope. It should be noted that any variations and substitutions equivalent to these embodiments should be considered to be covered within the scope of the claims. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
Claims
1. A multifunctional self-healing cement slurry system, characterized in that, include: Cement, self-healing agent in contact with carbon dioxide, solid toughening corrosion inhibitor, liquid elasticity anti-channeling agent, water loss reducing agent, defoamer, dispersant, retarder, water.
2. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, By weight, it includes: 100 parts cement, 2-18 parts carbon dioxide self-healing agent, 5-30 parts solid toughening corrosion inhibitor, 3-15 parts liquid elastic anti-channeling agent, 3-9 parts water loss reducing agent, 0.25-2 parts defoamer, 0.1-2.5 parts dispersant, 0.5-4.0 parts retarder, and 42-45 parts fresh water.
3. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The cement is a G / H grade high sulfur-resistant silicate cement that meets API standards.
4. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The self-healing agent upon contact with carbon dioxide is a mixture of rubber particles and gypsum, or a mixture of rubber particles and metal oxides, or a mixture of rubber particles, gypsum, and metal oxides.
5. The multifunctional self-healing cement slurry system according to claim 4, characterized in that, The mass ratio of the coated rubber particles, the gypsum, and the metal oxide is 3-15:2-10:1-5.
6. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The liquid elastic anti-channeling agent includes at least one of latex and resin liquid.
7. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The water loss reducing agent is an AMPS polymer.
8. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The dispersant is selected from one or both of sulfonated aldehyde-ketone condensate dispersants and polycarboxylic acid dispersants.
9. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The retarder includes at least one of organophosphate retarder and polymer retarder.
10. The multifunctional self-healing cement slurry system according to claim 1, characterized in that, The defoamer includes any one or more of phosphate ester defoamers, polyether defoamers, and silicone defoamers.
11. The method for preparing the multifunctional self-healing cement slurry system according to any one of claims 1 to 10, characterized in that, include: (1) Mix cement, carbon dioxide self-healing agent and solid toughness corrosion inhibitor into a mixed ash according to the proportion; (2) Dissolve the liquid elastic anti-channeling agent, water loss reducing agent, dispersant, retarder, and defoamer in water according to the proportion to obtain mixed water; (3) Under the first speed stirring, the mixed ash is added to the mixed water, and then stirred at the second speed to obtain a multifunctional self-healing cement slurry system.
12. The application of the multifunctional self-healing cement slurry system according to any one of claims 1 to 10 in CCUS, CCS, gas storage facilities, carbon dioxide flooding for enhanced oil recovery, development of acidic oil and gas fields, and high acidity scenarios of abandoned wells.